Re-Identifying Property in The Malaysian Penal Law - Wai, Wong Wai (Journal of Malaysian and Comparative Law, 2013)
The lack of legal recognition, acknowledgment on the significance, importance and the value of online resources such as information, data, keyword and meta-tags has caused them to be held in a vulnerable position and subjected to various forms of misuses and abuses. Currently the existing cyber-specified provisions are specifically focussed its main task of regulating illegal acts and activities occurring daily in cyberspace rather than protecting online resources. The lack of adequate legal protection for these online valuable resources is seriously affecting the level of confidence of internet users in conducting their business in cyberspace. One of these effective ways in protecting these online resources is to classify them as ‘property’. Any violation of such should be governed by the relevant penal provisions relating to property. In Malaysia, the penal provisions for offences against property has confined its applicability to corporeal and moveable property only, such penal provisions could not be used to protect online resources in that they are incorporeal and intangible in nature. The penal provision as such lacks its identity in classifying what property is and its definition. In proposing to extend the application of the Malaysian penal law to cyber cases relate to online resources, ‘property’ should further be redefined under the ‘bundle of rights’ theory. By defining property which consists of the bundle of rights and interests, this bundle theory would overcome the conceptual hurdle and that these online assets are to be regarded as property even though it lacks physical status and be accorded the same level of protection as any other type of property recognised by the law.